Winning the Oil Lottery: The Impact of Natural Resource Extraction on Growth - Tiago Cavalcanti; Daniel Da Mata; Frederik Toscani (European Regional Science Association (ERSA), 2014)
This paper studies the effect of oil discoveries on economic growth in Brazilian municipalities for the period from 1940 to 2000. It uses a unique identification strategy which exploits data on the drilling of approximately 20,000 oil wells in Brazil since oil explorations began in the country. We argue that oil discoveries are randomly assigned conditional on geological characteristics. The quasi-experimental outcome from drilling generates the treatment assignment: municipalities where oil was discovered during drilling constitute the treatment group while municipalities with drilling but no discovery are the control group. In our preferred specifications we find that oil discoveries increase per capita GDP by 25% over the 60-years period compared to the control group. Importantly, oil extraction has positive spillovers to other sectors of the economy. Services GDP per capita is estimated to increase by roughly 20% and urbanization by over 4% points. We show that the increase in services GDP per capita is mainly due to an increase in labor productivity. In line with intuition, these spillovers are present for onshore but not for offshore discoveries. Among other potential channels, the results are consistent with an increase in local demand for non-tradable services driven by the oil producing firm and highly paid oil workers.
Keywords: O13; O40; 330; Petroleum Industry; Economic Growth; Urbanization